Numerical and Experimental Approach to Evaluate Microplastic Transport in Saturated Porous Media - Hande Okutan; Çağdaş Sağır; Bedri Kurtuluş; Hasan Burak Özmen; Emrah Pekkan; Moumtaz Razack; Philippe Le Coustumer (Microplastics)
Under varying flow rate conditions, the transport and retention of polydisperse microplastics (MPls), with an average particle size of 16 ± 6 µm, were investigated in saturated porous media. First-order reversible and irreversible kinetic sorption models were used to describe the sorption kinetics. Sensitivity analyses provided insight into the effects of each sorption parameter. Both numerical modeling and experimental measurements were utilized to evaluate the retention rates of sand filters. The influence of flow rate on sorption was reflected in variations in the distribution coefficient (Kd), the mass transfer coefficient (β), and the irreversible sorption rate (K1). Lower flow rates were associated with higher Kd and β values, indicating increased sorption and reduced mass transfer rates. An increase in Kd resulted in a more gradual sorption process, with a decrease in peak concentration, whereas changes in β had a comparatively smaller impact on sorption rate and peak concentration. Lower K1 values were linked to higher peak concentrations and decreased retention efficiency. Numerical modeling revealed retention rates of 28 ± 1% at a flow rate of 31 mL min−1 and 17 ± 1% at 65 mL min−1. The introduction of MPls into saturated sand environments modifies the transport dynamics within the medium. Consequently, these alterations affect the hydrological characteristics of porous media, impacting groundwater quality and agricultural output. The mean absolute error (MAE) of 6% between the modeled and observed retention rates indicated a high level of accuracy. This study underscores the importance of examining retention efficiency and the accuracy of numerical models in understanding MPl transport in porous media.